2021
DOI: 10.1007/s11606-020-06483-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Readmission Among General Internal Medicine Patients Experiencing Homelessness

Abstract: BACKGROUND: People who are homeless have a higher burden of illness and higher rates of hospital admission and readmission compared to the general population. Identifying the factors associated with hospital readmission could help healthcare providers and policymakers improve post-discharge care for homeless patients. OBJECTIVE: To identify factors associated with hospital readmission within 90 days of discharge from a general internal medicine unit among patients experiencing homelessness. DESIGN: This prospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…In our cohort, unstable housing was associated with unplanned discharge. This is consistent with other studies, and highlights the vulnerability of this cohort, who may have competing demands and unique needs to support an inpatient stay [ 37 ]. Further opportunistic care may be directed at comorbid psychiatric conditions and cigarette smoking, which were both highly prevalent in this cohort.…”
Section: Discussionsupporting
confidence: 91%
“…In our cohort, unstable housing was associated with unplanned discharge. This is consistent with other studies, and highlights the vulnerability of this cohort, who may have competing demands and unique needs to support an inpatient stay [ 37 ]. Further opportunistic care may be directed at comorbid psychiatric conditions and cigarette smoking, which were both highly prevalent in this cohort.…”
Section: Discussionsupporting
confidence: 91%
“…This intervention was informed by a recent prospective cohort study conducted at the urban academic teaching hospital, which found that having an active case manager, sending discharge summaries to PCPs, and informal support were associated with reduced readmissions among homeless adults. 22 The first HOC position was created in February 2019 and has since been expanded to two positions and adapted through conversations with community partners and hospital staff. Ultimately, the goal of the Navigator Programme is to help homeless patients who are discharged from the hospital overcome systemic barriers and discontinuities in care that often result in poor health and high acute care utilisation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Indeed, there is abundant evidence suggesting that homeless adults rely heavily on acute care services, and rates of ED visits and hospitalisations are much higher among homeless versus non-homeless adults 18–21. A related problem is the high rate of hospital readmissions among homeless adults 18 19 22 23. Many of these readmissions are thought to be potentially preventable with more complete treatment and better coordination of health and social services following hospital discharge 24 25.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 4 ] Factors associated with readmission include improper discharge planning; failure to send the discharge plan to the primary care physician; poor follow-up practices, especially with primary care physicians; lack of social and community support; unclear instructions to patients on discharge; incomplete diagnosis; inadequately treated medical conditions; sub-optimal patient care; errors in medication reconciliation; drug interactions and side effects; frailty; malnutrition; severe chronic conditions; the persistence of underlying chronic conditions; lapses in communication between treating team members and the patient; poor management of self-care activities at home following discharge; inability in accessing health care and keeping appointments; incomplete patient education resulting in lack of awareness of whom to contact; where to go and how to manage symptoms at home; nosocomial infections; and poor adherence to medications due to cost or inaccessibility. [ 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 ] Contributory intrinsic factors include old age, high comorbidity burden, low literacy rate, low socio-economic status, and lack of social networks. [ 9 10 22 23 24 ] Patients discharged against medical advice are at a higher risk for early readmissions, usually within the first day following discharge (bounce-back readmissions).…”
Section: Introductionmentioning
confidence: 99%